Effects of Nutrition and Exercise Interventions on Persons with Sarcopenic Obesity: An Umbrella Review of Meta-Analyses of Randomised Controlled Trials - Reiter, Lea; Bauer, Silvia; Traxler, Mariella; Schoufour, Josje D; Weijs, Peter J M; Cruz-Jentoft, Alfonso; Topinková, Eva; Eglseer, Doris (Current obesity reports, 2023)
BACKGROUND: Sarcopenic obesity (SO) is an increasing phenomenon and has been linked to several negative health consequences. The aim of this umbrella review is the assessment of effectiveness and certainty of evidence of nutrition and exercise interventions in persons with SO. METHOD: We searched for meta-analyses of RCTs in PubMed, EMBASE and CENTRAL that had been conducted in the last five years, focusing on studies on the treatment and prevention of SO. The primary endpoints were parameters for SO, such as body fat in %, skeletal muscle mass index (SMMI), gait speed, leg strength and grip strength. The methodological quality was evaluated using AMSTAR and the certainty of evidence was assessed using GRADE. RESULTS: Four systematic reviews with between 30 to 225 participants were included in the umbrella review. These examined four exercise interventions, two nutrition interventions and four interventions that combined nutrition and exercise. Resistance training was the most frequently studied intervention and was found to improve gait speed by 0.14 m/s to 0.17 m/s and lower leg strength by 9.97 kg. Resistance, aerobic, mixed exercise and hypocaloric diet combined with protein supplementation is not significantly effective on selected outcomes for persons with SO compared to no intervention. The low number of primary studies included in the reviews resulted in moderate to very low certainty of evidence. CONCLUSION: Despite the lack in certainty of evidence, resistance training may be a suitable intervention for persons with SO, in particular for improving muscle function. Nevertheless, further research is necessary to strengthen the evidence.
Keywords: nutriční stav; GRADE approach; Meta-Analysis as Topic; Obesity; Review; terapie cvičením; Diet, Reducing; randomizované kontrolované studie jako téma; metaanalýza jako téma; obezita; Dietary protein; redukční dieta; Resistance training; lidé; Humans; Randomized Controlled Trials as Topic; Exercise Therapy; Nutritional Status; Sarcopenia; sarkopenie